NOSTALGIA IN SONG LYRICS: A SEMIOTIC ANALYSIS OF NIKI’S ‘HIGH SCHOOL IN JAKARTA’ - Mukminin, Muhamad Saiful (Universitas Nias Raya, 2024)
The present research uses a qualitative descriptive approach to explore the meanings and experiences of nostalgia contained in the lyrics of the song High School in Jakarta. The research data consists of the song lyrics as the primary data source. Data collection techniques include observation of the lyrics by noting relevant sections, literature review to understand the cultural context, and systematic text analysis. The data analysis process is conducted through three stages. First, a denotative analysis that examines the concrete elements in the lyrics, such as names, places, and events that reflect adolescent experiences. Second, a connotative analysis that delves into the emotions and deeper meanings behind the words used. Third, a myth analysis that identifies cultural myths present in the lyrics, such as societal views on adolescence and the role of social relationships in identity formation. The research findings indicate that this song serves as a reflective tool for listeners regarding adolescence, as well as how nostalgia is formed through lyrics rich in meaning and cultural context. In conclusion, semiotic analysis provides a deeper understanding of nostalgia as a strong emotional response rooted in the complexities of adolescence.